Anti-ischemic Effect of Monoterpene Citronellol on Experimental Stroke Models Mediated by Pro-inflammatory Cytokines - Liu, Xiao; Zhu, Chunji; Yin, Yong (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Phytomedicines are proven to treat various chronic diseases as these compounds are cost-effective with few or no side effects. Elucidating the ameliorative effect of phytomedicine on cerebral ischemia may be a potent alternative therapy. Citronellol, a monoterpene alcohol, is one such phyto compound present in the essential oils of Cymbopogon nardus and Pelargonium geraniums and has immense pharmacological properties such as antihyperalgesic, anticonvulsant and antinociceptive. Objective: In the present work, the anti-ischemic effect of citronellol in both cellular and animal models of stroke was analyzed. Methods: Citronellol-pretreated SH-SY5Y cells were subjected to oxygen-glucose deprivation and reperfusion. The cells were assessed for cell viability and LDH quantification. Inflammatory cytokines were estimated in the cell lysate of citronellol pretreated OGD-R induced cells. Healthy young SD rats were pretreated with citronellol and induced with MCAO-R. The control group was comprised of sham-operated rats treated with saline. Group II was comprised of MCAO/R-induced untreated rats. Groups III and IV rats were previously treated with 10 mg/kg and 20 mg/kg citronellol, respectively, for 7 consecutive days and induced with MCAO/R. Brain edema was analyzed by quantifying the water content and the percentage of infarct was assessed using the TTC staining technique. Acetylcholinesterase activity and neurological scoring were performed to assess the neuroprotective activity of citronellol. Lipid peroxidation and antioxidant levels were quantified to evaluate the antioxidant activity of citronellol. The anti-inflammatory activity of citronellol was assessed by quantifying proinflammatory cytokines using commercially available ELISA kits. Results: Citronellol treatment significantly ameliorated neuronal damage in both cellular and animal stroke models. Prior treatment of citronellol significantly decreased the inflammatory cytokines and increased the antioxidants. Citronellol treatment effectively protected the rats from MCAO/R-induced brain edema. Conclusion: Our results confirm that citronellol is an effective anti-ischemic drug with antioxidant and anti-inflammatory properties.
Keywords: Stroke